IMPLEMENTING REBT AT SCHOOL: THE IMPACT ACADEMIC ACHIEVEMENT AND EMOTIONAL WELL-BEING - Nisa, Khoirun; Abdullah, Abdullah; Jazilurrahman, Jazilurrahman; Sahidah, Ahmad; sugiono, sugiono (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Explores the application of Rational Emotive Behavior Therapy (REBT) in the school setting and its impact on student academic achievement and emotional well-being. The findings of this study provide in-depth insight into the benefits of implementing REBT in the school setting and provide a basis for developing more effective intervention approaches to improve student well-being and academic achievement. As a cognitive-based therapeutic method, REBT was implemented to identify and manage emotional and behavioral tendencies that might affect students academic achievement and emotional well-being. The research method involved applying REBT in an educational context and collecting data through surveys, interviews, and literary achievement analysis. The results of this study provide an in-depth look at the benefits of implementing REBT in a school setting and provide a basis for further development in understanding the relationship between emotional well-being, academic achievement, and psychological interventions in education. The practical implications of the findings can assist schools in designing programs that focus on student well-being and improving academic achievement through an integrated psychotherapeutic approach.